Demogenetic structure of brown trout Salmo trutta Linnaeus, 1758 populations in mountain headwaters: implications for conservation management. (19th March 2015) - Závorka, L.; Horký, P.; Kohout, J.; Kalous, L.; Slavík, O.
Summary: A demogenetic analysis based on 7 years of observation (2005–2011) was conducted to examine the population structure of brown trout Salmo trutta in pristine dendritic headwaters. The value of genetic divergence ( F ST ) among sampling units ranged from −0.03 to 0.16. Demographic synchrony was low or moderate, and the average correlation coefficient of population growth between sampling units ( r ¯ ) ranged from 0.28 to 0.66. No isolation by distance was observed, but genetic divergence was negatively correlated with demographic synchrony among sampling units. Variance in the population growth rate (i.e. local extinction probability) increased with distance from the mainstream and from other sampling units. In contradiction with the usual model of stream‐dwelling salmonids, the upstream sections of headwaters holds only ephemeral subpopulations, whereas the mainstream played a role in the source area of the metapopulation. These findings stress the importance of the mainstream in management conservation for brown trout in low productive mountain headwaters.